System for delivering microwave ablation to subcutaneous tumors in small-animals under high-field MRI thermometry guidance - Jan Sebek; Tej B. Shrestha; Matthew T. Basel; Faraz Chamani; Nooshin Zeinali; Ivina Mali; Macy Payne; Sarah A. Timmerman; Pegah Faridi; Marla Pyle; Martin O’Halloran; M. Conall Dennedy; et al. (International Journal of Hyperthermia)
Purpose Bio-effects following thermal treatments are a function of the achieved temperature profile in tissue, which can be estimated across tumor volumes with real-time MRI thermometry (MRIT). Here, we report on expansion of a previously developed small-animal microwave hyperthermia system integrated with MRIT for delivering thermal ablation to subcutaneously implanted tumors in mice.Methods Computational models were employed to assess suitability of the 2.45 GHz microwave applicators for delivering ablation to subcutaneous tumor targets in mice. Phantoms and ex-vivo tissues were heated to temperatures in the range 47–67 °C with custom-made microwave applicators for validating MRIT with the proton resonance frequency shift method against fiberoptic thermometry. HAC15 tumors implanted in nude mice (n = 6) were ablated in vivo and monitored with MRIT in multiple planes. One day post ablation, animals were euthanized, and excised tumors were processed for viability assessment.Results Average absolute error between temperatures from fiberoptic sensors and MRIT was 0.6 °C across all ex-vivo ablations. During in-vivo experiments, tumors with volumes ranging between 5.4–35.9 mm3 (mean 14.2 mm3) were ablated (duration: 103–150 s) to achieve 55 °C at the tumor boundary. Thermal doses ≥240 CEM43 were achieved across 90.7–98.0% of tumor volumes for four cases. Ablations were incomplete for remaining cases, attributed to motion-affected thermometry. Thermal dose-based ablative tumor coverage agreed with viability assessment of excised tumors.Conclusions We have developed a system for delivering microwave ablation to subcutaneous tumors in small animals under MRIT guidance and demonstrated its performance in-vivo.